EFEK DURASI PENYIMPANAN DI LEMARI PENDINGIN TERHADAP KADAR PROTEIN ASI PERAH - Arrafi, Muhammad Hafizh; Subandrate, Subandrate; Safyudin, Safyudin (Universitas Muhammadiyah Mataram, 2025)
Abstract: Exclusive breastfeeding is the best nutrition for babies to grow and develop. Currently, urban communities tend to stop breastfeeding at earlier age because of working mother. To overcome this, mothers can give expressed breast milk to babies by paying attention to the duration and temperature of storage, because it can affect the nutrients contained in breast milk. This study aims to determine the effect of the duration of storage of breast milk in the refrigerator on the protein contained in the breast milk. This research is a pure experimental research study with one group pre-test and post-test research design. The research was conducted at the Basic Medical Chemistry Laboratory, Faculty of Medicine, Universitas Sriwijaya. The number of expressed breastmilk samples in this study was 30 samples. Samples were divided into 5 groups, with variations in the duration of storage in the refrigerator (4-8°C) for 0 hour (control), 24 hours, 72 hours, 120 hours, and 192 hours. Protein level was measured by using Lowry method. Data were analyzed by repeated anova and paired t-test. The average protein content of ASIP at 0, 24, 72, 120, and 192 hours, respectively, was 2.93, 2.64, 2.61, 2.35, and 2.14 mg/dL (p=0,000 for repeated anova). The p values of the paired t-test storage durations of 24, 72, 120, and 192 hours, respectively, were 0.231, 0.137, 0.047 and 0.001. The duration of storage in the refrigerator that affects the protein levels of expressed breatmilk is 120 and 192 hours. Expressed breast milk protein levels significantly decrease after being stored in the refrigerator for 120 hours.Abstrak: ASI eksklusif adalah nutrisi terbaik bagi bayi untuk tumbuh dan berkembang. Saat ini masyarakat perkotaan cenderung menghentikan pemberian ASI pada usia yang lebih dini karena ibu bekerja. Untuk mengatasinya, ibu dapat memberikan ASI Perah (ASIP) pada bayi dengan memperhatikan durasi dan suhu penyimpanannya karena dapat mempengaruhi nutrisi yang dikandung ASI. Penelitian ini bertujuan untuk mengetahui efek durasi penyimpanan di lemari pendingin terhadap kadar protein ASI perah. Studi ini merupakan penelitian eksperimental murni (true ekseperimental) dengan desain penelitian one group pretest and posttest. Pemeriksaan kadar protein dilakukan di Laboratorium Kimia Dasar Kedokteran Fakultas Kedokteran Universitas Sriwijaya, dengan total sampel 30 sampel ASIP. Sampel dibagi menjadi 5 kelompok, dengan variasi durasi penyimpanan dalam lemari pendingin (4-8°C) selama 0 jam (kontrol), 24 jam, 72 jam, 120 jam, 192 jam. Uji kadar protein dengan metode Lowry. Data dianalisis dengan repeated annova dan paired t-test. Rata-rata kadar protein ASIP secara berturut-turut pada 0, 24, 72, 120, dan 192 jam adalah 2,93, 2,64, 2,61, 2,35, dan 2,14 mg/dL dengan hasil uji repeated anova p=0,000. Nilai p dari paired t-test masing-masing durasi penyimpanan 24, 72, 120, dan 192 jam adalah 0,231, 0,137, 0,047 dan 0,001. Lama penyimpanan dalam lemari es yang mempengaruhi kadar protein ASI perah adalah 120 dan 192 jam. Kadar protein ASI perah mengalami penurunan signifikan setelah disimpan dalam lemari pendingin selama 120 jam.